Understanding and creating art - Goldstein, Ernest 1933-. (Dallas Garrard Pub., 1986)
Discusses some important paintings and sculpture in terms of design elements and also from the viewpoint of the artist. Includes questions and art activities.
Keywords: Painting -- Psychological aspects; Composition (Art).; Visual perception